2004
DOI: 10.1039/b405782a
|View full text |Cite
|
Sign up to set email alerts
|

The deactivation pathways of the excited-states of the mycosporine-like amino acids shinorine and porphyra-334 in aqueous solution

Abstract: In vitro studies on the structurally related mycosporine-like amino acids (MAAs) porphyra-334 and shinorine in aqueous solutions were carried out aiming at their full photochemical and photophysical characterization and expanding the evidence on the assigned UV-photoprotective role of the molecules in vivo. The experiments on shinorine confirmed a high photostability and a poor fluorescence quantum yield, in concordance with previous results on porphyra-334. The estimation of triplet production quantum yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
114
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 32 publications
18
114
0
5
Order By: Relevance
“…In cyanobacteria, MAAs protect the cells against solar radiation [28,29]. The energy absorbed by MAAs is promptly dispersed into the surroundings as heat [30,31]. Thus, MAAs do not function as accessory pigments in photosynthesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…In cyanobacteria, MAAs protect the cells against solar radiation [28,29]. The energy absorbed by MAAs is promptly dispersed into the surroundings as heat [30,31]. Thus, MAAs do not function as accessory pigments in photosynthesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…[36]) only shinorine has been reported to fluoresce; ref. [37,38]). This, perhaps, relates to shinorine being a cyclohexenimine derivative, while the other two MAAs are cyclohexenone derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that these mechanisms are inversely coupled in Heterocapsa sp. Under N-replete conditions, UVR stimulated MAA accumulation, with the consequent energy dissipation as heat (Conde et al 2004). However, under N limitation, MAA content decreased but the deepoxidation degree of the xanthophyll cycle pigments increased.…”
Section: Discussionmentioning
confidence: 99%
“…The protection from harmful UVR by MAAs is because of their UV-screen properties (Conde et al 2004; Korbee et al 2006) and their antioxidant scavenging capacity (Dunlap and Yamamoto 1995;de la Coba et al 2009). A correlation between MAAs and in situ irradiance levels has been noticed in many locations and in a wide variety of organisms (Korbee et al 2006).…”
mentioning
confidence: 99%